2017
DOI: 10.1021/acs.energyfuels.7b00405
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of Residual Tobacco Seeds: Characterization of Nitrogen Compounds in Bio-oil Using Comprehensive Two-Dimensional Gas Chromatography with Mass Spectrometry Detection

Abstract: Energetic tobacco (EnT) is a type of genetically modified tobacco with a focus on energy. Its seeds are larger and appear in greater quantity than those of conventional tobacco. This plant easily adapts to unproductive soils and is practically free of nicotine. The oil seed from EnT can be used for producing biodiesel without competition with edible oils. Additionally, the resulting residual cake can be thermally degraded to bio-oil and biochar through pyrolysis processes. In this study, the fast pyrolysis (70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
2
14
0
1
Order By: Relevance
“… a Links to references: , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , and . …”
Section: Principles Of Two-dimensional Gas Chromatographyunclassified
“… a Links to references: , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , , and . …”
Section: Principles Of Two-dimensional Gas Chromatographyunclassified
“…The exciting principle behind twodimensional GC Â GC TOFMS is the separation of mixtures by the polarity of species compared to one-dimensional GC-MS separation based on the compounds' boiling point. [28][29][30]36 There are very few studies in the literature regarding the analysis of tire oil fractions using this advanced chromatographic technique. Ngxangxa reported that TPO is a complex mixture of C 6 -C 24 compounds, including paraffins, terpenes, monocyclic and PAHs, heterocyclic compounds, etc.…”
Section: Two Dimensional Gas Chromatography Time-of-ight Mass Spectrmentioning
confidence: 99%
“…One dimensional GC has been used for many years; however, there remain minor shortcomings in obtaining the best compound separation using this technique. Increasing the resolution and detectability of liquid oil could be obtained using higher-dimensional GC techniques [27], allowing for the detection of a higher number of compounds. A 2-dimensional, GCxGC/TOF MS analysis is believed to be more efficient in identifying more organic compounds in the organic fraction than traditional GC-MS.…”
Section: Introductionmentioning
confidence: 99%